From Bataille to Badiou : Lignes, the preservation of radical French thought, 1987-2017 - MAY, ADRIAN (Contemporary French and francophone cultures., 2018)
This exhaustive reading of the review Lignes provides the first in depth study of a French intellectual periodical publication form the 1980s to the contemporary moment. It demonstrates the preservation and development of 'French Theory' into the new millennium, and provides a new cultural history of France, from the fall of the Berlin Wall to the 2016 terror attacks.